Planning roadside landscape for noise and emissions control - Li, Rui (Nanyang Technological University, 2020)
This project verified the effectiveness of reducing exhaust pollutants and traffic noise on two shrubs on the NTU campus. The traffic pollution status at two experimental sites and the effectiveness of the two shrubs in reducing traffic pollution are compared and evaluated. Suggestions and recommendations on roadside landscape planning are provided. The tested Ixora Siamensis shrub exhibits a better ability to reduce the concentration of PM10, 34% higher than the one at another site. If it is designed as a green barrier that reaches the height of an adult human ears, its noise reduction ability is expected to exceed 11 dB, while noting that the lower portions of the green barrier are more resistant to traffic emissions, which has the root portion up to the tailpipe height still considering dense after long-term exposure to traffic pollution. Another type of shrub, Ehretia microphylla Lam shrub, has comparatively higher noise reduction efficiency as close to the theocratical expected value mainly due to twice the height of the tested Ixora Siamensis shrub, relatively denser biological structure, and hairy leaves and stems.In addition, its growth rate is relatively faster so more frequency of the pruning service is needed. However, the root system of this type of shrub is less tolerant to traffic exhaust, so it is an excellent noise-reducing crop while its ability to reduce traffic emission is weak. In general, the PM2.5 and chemical pollutant concentration at the two sites were both far below the NEA stadard and neglectable respectively. Therefore, the effectiveness of these two shrubs on these two parameters is not applicable in the context of this experiment. Taking into account the disadvantages of Ixora Siamensis bushes, regular root maintenance is recommended to keep the barrier structure higher than the height of human ears. It was also recommended the sandwich layered barrier design with anti-collision guard plate inserted in the shrub body. In addition, full consideration of tailpipe position design that locates tailpipe at the rear right of vehicle body or face the sky is beneficial as well.